Canadian Experience in the Application of Paste and Thickened Tailings for Surface Disposal - Oxenford, J; Lord, ER (Paste 2006: Ninth International Seminar on Paste and Thickened Tailings, 2006)
Canada has long been one of the worlds major mining centres and has been at the forefront in the development and application of paste and thickened tailings technology for surface disposal of fine-grained tailings waste. In 1973 under the guidance of Dr. E. Robinsky, the first thickened tailings operation for surface disposal was inaugurated at the Kidd Operation in Ontario. Over the years, thickening improvements have been implemented and today Kidd ranks as the longest operating thickened tailings surface disposal site in the world.